2014
DOI: 10.1002/ijc.28678
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived microparticles induce bone marrow-derived cell mobilization and tumor homing: A process regulated by osteopontin

Abstract: Acute chemotherapy can induce rapid bone-marrow derived pro-angiogenic cell (BMDC) mobilization and tumor homing, contributing to tumor regrowth. To study the contribution of tumor cells to tumor regrowth following therapy, we focused on tumor-derived microparticles (TMPs). EMT/6 murine-mammary carcinoma cells exposed to paclitaxel chemotherapy exhibited an increased number of TMPs and significantly altered their angiogenic properties. Similarly, breast cancer patients had increased levels of plasma MUC-1 1 TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…The importance of these particles in systemic signalling is supported by the finding that their circulating levels in tumour-bearing hosts seem to be higher than the levels observed in cell culture experiments where microvesicle-induced effects have been clearly observed 65 .…”
Section: Tumour-driven Systemic Processes That Affect Primary Tumour mentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of these particles in systemic signalling is supported by the finding that their circulating levels in tumour-bearing hosts seem to be higher than the levels observed in cell culture experiments where microvesicle-induced effects have been clearly observed 65 .…”
Section: Tumour-driven Systemic Processes That Affect Primary Tumour mentioning
confidence: 97%
“…Likewise, renal-carcinoma-derived exosomes were found to promote angiogenesis in lung tumour metastases 64 . Additionally, a study of murine mammary carcinoma demonstrated that osteopontin, carried through the circulation by tumour-derived microparticles, was necessary to mobilize pro-angiogenic cells from the bone marrow 65 . Interestingly, in these experiments, the mammary tumours produced microparticles as a result of paclitaxel chemotherapy, which was consistent with the authors’ clinical observations that circulating microparticle numbers were elevated in some cancer patients following chemotherapy.…”
Section: Tumour-driven Systemic Processes That Affect Primary Tumour mentioning
confidence: 99%
“…Although OPN depletion from MP is not sufficient to reduce tumor growth, they observed that when bone marrow-derived pro-angiogenic cells (BMDC) from paclitaxel-treated mice were injected into OPN-depleted tumor-bearing mice, tumor growth and BMDC infiltration were greatly inhibited (Fremder et al 2014). These data suggest that OPN-loaded MPs may play important roles in tumor homing and BMDC mobilization, which facilitates angiogenesis.…”
Section: Osteopontinmentioning
confidence: 82%
“…Recently, Fremder et al (2014) detected a high OPN content in tumor cell-derived MP. Although OPN depletion from MP is not sufficient to reduce tumor growth, they observed that when bone marrow-derived pro-angiogenic cells (BMDC) from paclitaxel-treated mice were injected into OPN-depleted tumor-bearing mice, tumor growth and BMDC infiltration were greatly inhibited (Fremder et al 2014).…”
Section: Osteopontinmentioning
confidence: 98%
“…It has been shown that microparticles from paclitaxel treated breast carcinoma cells contain osteopontin by which they induce BM-derived pro-angiogenic cell mobilization and colonization, leading to microvessel sprouting and increased angiogenesis, which ultimately accelerates tumor growth [86]. In a different study, the anti-VEGF-A antibody B20 reduced the level of VEGF-A enclosed in breast cancer cell-secreted microparticles and these vesicles were unable to activate endothelial cells and could not promote BM-derived pro-angiogenic cell colonization [87].…”
Section: Effect Of Tumor-derived Evs On Bm-derived Cellsmentioning
confidence: 99%